Micro spherical anatase phase TiO2 thin films for room temperature operated formaldehyde gas sensor applications - D. Rajkumar; H. Umamahesvari; P. Nagaraju (Results in Chemistry, 2023)
A highly sensitive and selective gas sensor is crucial for detecting hazardous gases in the environment at room temperature (RT). Titanium dioxide (TiO2) shows promise as an excellent candidate for gas sensing due to its superior sensitivity and stability, even in robust conditions. TiO2 could potentially replace volatile organic compound (VOC) gas sensors. This study employed the spray pyrolysis technique to deposit titania thin films. The precursor solution was sprayed onto substrates at temperatures ranging from 375 °C to 450 °C in 25 °C increments. A temperature-dependent study was conducted on TiO2 thin films to examine their structural, optical, and topographical properties. Films deposited at 400 °C and above exhibit a crystalline anatase phase. Higher deposition temperatures resulted in the decreased band gap of TiO2 films. TiO2 films showed excellent response to formaldehyde concentrations (1–25 ppm) and high selectivity over other reducing gases (methanol, ethanol, butanol, toluene, xylene), even at room temperature. Microstructural, optical, and morphological analyses provided valuable insights into the gas sensing mechanism, enhancing understanding of film functionality.